Male aggression, limited female choice and the ontogeny of mating behaviour in the flesh fly Sarcophaga crassipalpis. (19th October 2015) - Dylan Shropshire, J.; Moore, Darrell; Seier, Edith; Joplin, Karl H.
Abstract: Previous work has shown that male flesh flies ( Sarcophaga crassipalpis Macquart) exhibit an ontogeny of behaviour from eclosion through sexual maturity that includes extensive changes in the expression of aggressive, non‐aggressive interactive and non‐interactive behaviours. To determine how the presence of a female flesh fly influences the manifestation of these behaviours, male flesh flies of different ages post‐eclosion are paired with same‐age females and their behaviours are monitored in a simple arena during a 50‐min observation period. All flies are socially isolated until pairing. Although the levels of expression of aggressive and non‐aggressive interactive behaviours are depressed relative to previous findings in male‐opponent pairs, the ontogeny of aggression still occurs as indicated by a significant increase, with age, in the agonistic behaviour ' hold '. Similar to male‐opponent pairs and individual males, the performance by males of the non‐interactive behaviours ' walking ' and ' standing ' diminishes, whereas ' upside‐down ' increases with age. By contrast, ' grooming ' shows a significant age‐related decline. No courtship behaviours are observed in the males, although the aggressive behaviour ' hold ' is a significant transition to mating. Females show no obvious courtship or rejection behaviours, although the significant increase in ' upside‐down ' with age could possibly be a behavioural gateway to mating. The results of this study indicate that extensive age‐related changes encompassing the entire behavioural repertoire are intrinsic to male flesh flies and persist under a variety of different social contexts.